2020
DOI: 10.1103/physrevd.102.025012
|View full text |Cite
|
Sign up to set email alerts
|

Field theory of dissipative systems with gapped momentum states

Abstract: We develop a field theory with dissipation based on a finite range of wave propagation and associated gapped momentum states in the wave spectrum. We analyze the properties of the Lagrangian and the Hamiltonian with two scalar fields in different representations and show how the new properties of the twofield Lagrangian are related to Keldysh-Schwinger formalism. The proposed theory is non-Hermitian, and we discuss its properties related to PT symmetry. The calculated correlation functions show a decaying osci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…The thermal waves reveal a collective liquid response (i.e., long range intermolecular interactions). This is in agreement with recent experimental and theoretical results indicating that liquids support shear waves at low scale [ 11 , 12 , 13 , 14 , 17 , 19 , 20 , 21 , 22 ], and experimentally identified in various simple and complex fluids [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Low frequency shear elasticity measures the strength of the intermolecular interactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The thermal waves reveal a collective liquid response (i.e., long range intermolecular interactions). This is in agreement with recent experimental and theoretical results indicating that liquids support shear waves at low scale [ 11 , 12 , 13 , 14 , 17 , 19 , 20 , 21 , 22 ], and experimentally identified in various simple and complex fluids [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Low frequency shear elasticity measures the strength of the intermolecular interactions.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that the strong liquid/substrate interaction amplifies the fluid response to a mechanical field and has revealed the existence of a mesoscopic “static” shear elasticity (0.1–10 Hz) in various fluids including polymer melts and molecular liquids [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The shear elasticity of fluids is a scale dependent property, the force of which increases as the probed scale decreases [ 11 , 12 , 13 , 14 ]. Figure 1 illustrates the spectacular transition from viscous (the viscous modulus G ” scaling with the square of the frequency ω 2 ) to an elastic-like response (the shear modulus G ’ dominates and is independent of the frequency) of the mesoscopic mechanical response of the glycerol in standard conditions and when using a high wetting substrate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This equation has been recently extensively discussed in the context of liquids dynamics and it gives rise to the so-called gapped momentum states [116], which have been observed in holographic models [79,117]. This relation, which can be obtained using quasi-hydrodynamics [118] and field theory for dissipative systems [119], implies that the shear diffusive mode (54) survives only up to a certain cutoff momentum:…”
Section: Causality Of Relativistic Hydrodynamics As a Diffusivity Boundmentioning
confidence: 98%
“…This equation has been recently extensively discussed in the context of liquids dynamics and it gives rise to the so-called gapped momentum states [114], which have been observed in holographic models [76,115]. This relation, which can be obtained using quasi-hydrodynamics [116] and field theory for dissipative systems [117], implies that the shear diffusive mode (53) survives only up to a certain cutoff momentum:…”
Section: Causality Of Relativistic Hydrodynamics As a Diffusivity Boundmentioning
confidence: 98%